Cationic switchable lipids: pH-triggered molecular switch for siRNA delivery. Issue 1 (1st December 2016) - Viricel, W.; Poirier, S.; Mbarek, A.; Derbali, R. M.; Mayer, G.; Leblond, J.
Abstract : siRNA delivery materials based on cationic switchable lipids are demonstrated. A pH-sensitive molecular switch able to change its conformation upon protonation at endosomal pH values is embedded into the structure of cationic lipidoid materials, thus conferring endosomal escape properties. Abstract : A pH-sensitive molecular switch able to change its conformation upon protonation at endosomal pH values is embedded into the structure of cationic lipidoid materials, thus conferring endosomal escape properties. Involvement of the conformational switch in the endosomal escape process was confirmed and leading material identified was able to induce efficient gene knockdown both in vitro and in vivo . The lipid nanoparticles reported here are promising for therapeutic applications and this work could serve as a template for future design of stimulus-responsive (ionic, redox, light) molecular switch for drug and gene delivery.